Long-Term Survival Analysis of Transarterial Chemoembolization Plus Radiotherapy vs. Radiotherapy for Hepatocellular Carcinoma With Macroscopic Vascular Invasion - Su, Ting-Shi; Li, Li-Qing; Meng, Wan-Wan; Wang, Yu-Dan; Chen, Yi-Tian; Li, Jian-Xu; Du, You-Qin; Qu, Song; Zhao, Chang; Huang, De-Jia; Liang, Shi-Xiong; Li, Le-Qun (Frontiers in Oncology, 2020)
Background: Macroscopic vascular invasion (MVI) is a terminal manifestation of hepatocellular carcinoma (HCC) and carries an extremely poor prognosis. In Chinese and Korean HCC guidelines, transarterial chemoembolization (TACE), or/and radiotherapy (RT) is adopted for treatment of MVI. In the current study, we aimed to compare the long-term outcome of TACE + RT to that of RT alone in patients with local advanced HCC with MVI. Methods: In this retrospective study, 148 treatment-naive patients of HCC with MVI were enrolled. Of the patients enrolled, 49 received TACE + RT treatment, whereas 99 patients received RT alone as a monotherapy. Overall survival (OS), progression-free survival (PFS), and intrahepatic control were evaluated using univariable and propensity score–matched analyses. Results: During follow-up, 126 patients (85.1%) died. The median follow-up time was 55.0 months in the RT group and 57.0 months in the TACE + RT group. The TACE + RT group showed better OS and PFS than the RT group, but intrahepatic control was comparable in these two groups. Of 41 cases well-pairs after propensity score matching, the associations between TACE + RT and better OS and PFS remained (15.0 vs. 8.0 months, and 8.0 vs. 4.0 months, all P < 0.05). The 1-, 2-, 3-, and 5-years OS rates in the TACE + RT group were 56.1, 28.6, 20.8, and 15.7 vs. 31.5%, 13.1%, 9.8%, and 6.7% in the RT group, respectively (P = 0.017). The 6-, 12-, and 24-months rates in the TACE + RT group were 51.2, 39.0, and 23.1% vs. 36.6%, 13.9%, and 11.1% in the RT group, respectively (P = 0.04). Two patients (4.1%) experienced radiation-induced liver disease (RILD), and one (2.0%) experienced RT-related gastrointestinal (GI) bleed in the TACE + RT groups. Nine patients (9.1%) experienced RILD, and two (2.0%) experienced RT-related GI bleed in the RT groups. Conclusion: Transarterial chemoembolization + RT had well-complementarity with no more complications than RT alone, providing a better PFS and OS compared with RT-alone treatment for HCC with MVI.